Estimating the Net Energy Value of Expelled, Extruded Soybean Meal When Fed to Nursery Pigs - Allison K. Blomme; Haley K. Wecker; Mike D. Tokach; Jason C. Woodworth; Charles R. Stark; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2021)
Solvent-extracted soybean meal (SSBM) is typically used as the primary protein source in swine diets in the United States. Mechanically extracted or expelled soybean meal (MSBM) typically has increased concentrations of fat and decreased concentrations of essential AA compared to SSBM, but MSBM has been demonstrated to have improved AA digestibility. This study aimed to estimate the NE value of MSBM relative to SSBM and to determine its effects on growth performance of late nursery pigs. A total of 297 pigs (241 × 600, DNA) were weaned (BW 11.2 lb) and placed into 60 pens (2 rooms of 30 pens) with 5 pigs per pen balanced by gender and weaning weight. Pigs were fed a common diet for 21 days. Then, pens of pigs (BW 20.7 lb) were randomly assigned to one of five treatments to provide 12 replications per treatment. Treatments consisted of increasing amounts of MSBM replacing SSBM in the diet (0, 25, 50, 75, and 100%). All diets were fed for 28 days and were formulated to 1.30% standardized ileal digestible lysine, and met or exceeded NRC2 recommendations for Lys:AA, Ca, and P. The SSBM has an NRC2 NE value of 946 kcal/lb and the 0% MSBM diet was formulated to 1091 kcal/lb and NE was not balanced between diets. Analyzed values for CP, ether extract, crude fiber, and total Lys for the SSBM were 47.28%, 0.47%, 3.80%, and 3.00%, respectively, while the MSBM contained 47.41%, 6.88%, 5.32%, and 2.99% respectively. The MSBM had increased values for KOH solubility and trypsin inhibitor (83.62 and 7026 TIU/g, respectively) compared to the SSBM (73.05 and 3011 TIU/g, respectively) while urease activity was similar between the two (0.03 vs. 0.02 Δ pH, respectively). Data were analyzed using PROC GLIMMIX (SAS v. 9.4) with pen as the experimental unit and room as the blocking factor. There was no evidence of differences in ADG and ADFI in pigs fed diets with increasing concentrations of MSBM. Pigs fed diets with increasing concentrations of MSBM had improved (linear,P<0.001) F/G and caloric efficiency on an NE basis. In conclusion, using caloric efficiency to estimate NE of the MSBM relative to SSBM, MSBM was estimated to have a value of 123% of SSBM NE or 1,164 kcal/lb. This increase in NE resulted in improved feed efficiency of nursery pigs.
Keywords: nursery pigs; soybean meal; extruded-expelled soybean meal; caloric efficiency